2020
DOI: 10.1049/ipr2.12010
|View full text |Cite
|
Sign up to set email alerts
|

Image denoising method based on variable exponential fractional‐integer‐order total variation and tight frame sparse regularization

Abstract: This study presents a variational image restoration algorithm based on variable exponential fractional‐order total variation (TV), variable exponential integer‐order TV and tight frame sparse regularization. The energy functional of this variational problem is composed of four parts: a fractional‐order TV regularization term with a variable exponent, an integer‐order TV regularization term with a variable exponent, a data fidelity term and a tight frame regularization term. The variable exponent is a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Wang Y. and other researchers proposed to use variable exponential fractional reciprocal, integer reciprocal, and book writing regularization methods to achieve ID while preserving the texture details of the image. Research has shown that this method has strong robustness to noise [9]. Usui K. and other researchers used the denoising convolutional neural network (DnCNN) of convolutional neural network as a general CNN model and used it for transfer learning to denoise images.…”
Section: Related Workmentioning
confidence: 99%
“…Wang Y. and other researchers proposed to use variable exponential fractional reciprocal, integer reciprocal, and book writing regularization methods to achieve ID while preserving the texture details of the image. Research has shown that this method has strong robustness to noise [9]. Usui K. and other researchers used the denoising convolutional neural network (DnCNN) of convolutional neural network as a general CNN model and used it for transfer learning to denoise images.…”
Section: Related Workmentioning
confidence: 99%
“…Stepping into the 21st century, the development of computer science and technology is changing day by day, in which the processing and analysis of digital images have formed a unique scientific system [ 1 ]. In the processing and analysis of digital images, image segmentation (IS) is a key part [ 2 ]. However, effective image segmentation is not easy to realize in adaptive image processing due to insufficient a priori information and imaging noise [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate this issue, Li et al [5] proposed a TV model with variable exponents which can automatically adjust the norm of the gradient according to the features of different regions. With the expectation to remove noises and retain the details of the image simultaneously, the methods [6,7,8] selected the L1-norm as the regularization term for the edge of the image, and the L2-norm as the regularization term for the smooth regions, respectively. Although the adoption of variable exponents has reduced the staircasing effect of TVbased methods to a certain extent [5], their abilities to protect edge information are restrained by taking the L2-norm as the fidelity term.…”
Section: Introductionmentioning
confidence: 99%